A relação entre os valores organizacionais, as práticas e a confiança dos clientes em organizações do setor de serviços - Guardani, Fátima (2008)
This study had the objective to analyze the relation among the organizational values, the practices and the trust of the costumers in services organizations. Due to values influence in behavior; to organizational values influence in organizations members choices and decisions, and in the development of organizational practices, it was aimed to investigate, in the services organizations costumers point of view, the relation among organizational values, organizational practices noticed in the interaction with the employees, and the trust in organizations.To fulfil the study, the elaboration and application of a scale related to organizational practices noticed by costumers in interaction with employees was carried out, as well as the adaptation and application of a scale related to organizational values, and another referring to the analysis of trust. The sample, characterized as non-probabilistic, resulted in 503 services organizations costumers. The data treatment involved multivariate data analysis. The results evidenced that the organizational values noticed by costumers, positively correlated with their trust in organizations, involved respect with stakeholders, welfare of the employees, prestige and tradition. The organizational practices noticed by costumers in the interaction with employees, positively correlated with costumers trust in organizations refer, basically, to the positive interaction and the practices related to the competitors. The costumers´ trust was composed partially by the dispositional trust and mainly by the trust given to the organizations, composed by trust based on knowledge, characteristics and identification. New researchs are suggested, involving costumers of others segments and services organizations, using clusters analysis; comparison between the organizational values shared by employees and those noticed by costumers, as well as comparison between organizational values noticed by costumers and their personal values.